2013
DOI: 10.4103/2211-4122.123953
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of left ventricular dysfunction in diabetes mellitus patients with normal ejection fraction, stratified by BMI: A preliminary speckle tracking echocardiography study

Abstract: Background:Diabetes mellitus (DM) represents by itself a major risk factor for cardiovascular events and the coexistence of obesity with consequent left ventricular volumetric overload could be responsible for further damages on left ventricular function. Aim of this study was to demonstrate the effect of body mass index (BMI) on left ventricular function in diabetes patients with no cardiovascular complications and with normal ejection fraction (EF).Materials and Methods:We evaluated 71 stable asymptomatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
1
15
2
Order By: Relevance
“…Our results found no statistically significant difference between the three groups as regarding demographic data and risk factors. This was contrary to Conte L. et al [6] who measured the degree of longitudinal fibers dysfunction by STE in diabetic and obese patients and found reduction in GLPS in those patients. Also, Rostamzadeh et al stated that of conventional risk factors, diabetes mellitus (55%) and hypertension (67%) were more frequent in the high-risk group when compared with low-risk and normal groups [1].…”
Section: Discussioncontrasting
confidence: 82%
“…Our results found no statistically significant difference between the three groups as regarding demographic data and risk factors. This was contrary to Conte L. et al [6] who measured the degree of longitudinal fibers dysfunction by STE in diabetic and obese patients and found reduction in GLPS in those patients. Also, Rostamzadeh et al stated that of conventional risk factors, diabetes mellitus (55%) and hypertension (67%) were more frequent in the high-risk group when compared with low-risk and normal groups [1].…”
Section: Discussioncontrasting
confidence: 82%
“…The longitudinal subendocardial fibers dysfunction in diabetes/obese patients could be derived by the complex interaction between metabolic (diabetes) and hemodynamic/endocrine abnormalities. [18] In the present study, hyperglycemia has shown to increase the LVMI since MS patients with mean FBS ≤ 140 mg/dl had highest mean LVMI (53.72 ± 27.91 g/m 2.7 ) than hypertensive patients (40.48 ± 14.13 g/m 2.7 ) [Table 3]. Grossman et al .…”
Section: Discussionmentioning
confidence: 54%
“…After the load is elevated due to elevated vascular resistance caused by excess adipose tissue and higher artery stiffness. [18] This study has showed that high BMI increases LVMI since MS patients with BMI > 30 had highest mean LVMI (51.14 ± 22.08 g/m 2.7 ) than MS patients with BMI < 30 had least (38.35 ± 8.52 g/m 2.7 ) [Table 3]. Schirmer et al .…”
Section: Discussionmentioning
confidence: 98%
“…After studying diabetic patients with a free history of cardiovascular disease and with preserved ejection fraction, researchers concluded that increased body weight induced subclinical alteration in longitudinal deformation, precisely detected by STE. As a result, we notice that while DM causes a subtle and global deterioration in cardiac function before symptoms occur, obesity further hampers proper systolic and diastolic function [ 25 ].…”
Section: Global Longitudinal Strain (Gls)mentioning
confidence: 99%